Irelands manufactured exports to EEC and common external tariff - McAleese, D; Martin, J (Economic & Social Studies, 1972)
One of the most remarkable features of Ireland's post-war trade structure has been the rapid increase of manufactured exports, both in absolute terms and relative to total exports. The average annual growth rate of manufactured exports during the last two decades has exceeded 19 per cent in current value terms, more than twice the growth rate of total Irish exports.The share of manufactured exports in total merchandise exports has increased from 6 per cent in 1950, to 19 per cent in 1959 and has risen still further, to 37 per cent, in 1971.
Keywords: Irish Exports; EEC